Crystal of phosphorus compound and method for producing the same

A phosphorus compound with a specific X-ray diffraction pattern, produced through controlled crystallization, addresses handling issues in epoxy resin applications by maintaining composition integrity and flame retardancy.

JP2025016928APending Publication Date: 2025-02-05ADEKA CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023119742
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-24
Publication Date
2025-02-05

AI Technical Summary

Technical Problem

Existing phosphorus compounds used as flame retardants for epoxy resin face handling difficulties, leading to issues such as bleed phenomena and decreased physical properties of cured objects.

Method used

Development of a phosphorus compound with a specific X-ray diffraction pattern, characterized by a maximum peak intensity ratio within certain diffraction angles, which is produced through a method involving the use of organic solvents and controlled crystallization processes.

Benefits of technology

The phosphorus compound exhibits excellent handling properties, preventing bleed phenomena and maintaining the physical properties of epoxy resin compositions, making it an effective flame retardant.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025016928000014
    Figure 2025016928000014
  • Figure 2025016928000015
    Figure 2025016928000015
  • Figure 2025016928000016
    Figure 2025016928000016
Patent Text Reader

Abstract

To provide a crystal of a phosphorus compound with superior handleability.SOLUTION: The present invention provides a crystal of a phosphorus compound represented by formula (1), where the ratio (A / B) of the maximum peak intensity (A) within the diffraction angle (2θ) range of 16.00°-16.80° to the maximum peak intensity (B) within the diffraction angle (2θ) range of 17.40°-18.20° in a diffraction pattern derived from X-ray diffraction is 1.50 or more and 3.00 or less. (In the formula, n is 0 or a positive number.)SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a crystalline substance of a phosphorus compound and a method for producing the same, and more particularly to a crystalline substance of a phosphorus compound having a specific X-ray diffraction pattern in powder X-ray diffraction and a method for producing the same. [Background technology]

[0002] Epoxy resins are used in a wide range of industrial applications, and the performance required of epoxy resins has become increasingly sophisticated in recent years with the development of industry. For example, epoxy resins have been used for copper-clad laminates and casting materials used in electronic components and electronic devices. Brominated epoxy resins, which provide flame retardant effects from the standpoint of safety, such as preventing fires and retarding the spread of fire, have been used for these epoxy resins.

[0003] Meanwhile, as prior art for imparting flame retardancy to epoxy resins, methods using a wide variety of organic phosphorus compounds have already been presented. In order to achieve flame retardancy, one effective means is to increase the phosphorus content in the composition, and a method of adding a flame retardant with a high phosphorus content to an epoxy resin composition is known (for example, Patent Document 1).

[0004] Furthermore, a resin composition has been proposed in which a dialkylphosphinate salt is added to a thermoplastic polyester resin as a phosphorus compound that exhibits high flame retardancy (for example, Patent Document 2). Furthermore, a curable epoxy resin composition containing a phosphorus-containing compound reactive with an epoxy group has been proposed (for example, Patent Document 3). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2004-051907 A [Patent Document 2] JP 2010-037375 A [Patent Document 3] International Publication No. 2015 / 049965 Summary of the Invention [Problem to be solved by the invention]

[0006] However, although the phosphorus-containing compound described in Patent Document 3 can impart flame retardancy to an epoxy resin, it has a problem in that it is difficult to handle due to its deliquescent nature.

[0007] Therefore, an object of the present invention is to provide a phosphorus compound that is easy to handle. [Means for solving the problem]

[0008] As a result of extensive investigations, the present inventors have found that a phosphorus compound having a specific X-ray diffraction pattern is easy to handle, and have arrived at the present invention.

[0009] That is, the present invention is a crystalline form of a phosphorus compound represented by the following formula (1), in which the ratio (A / B) of the maximum peak intensity (A) within a diffraction angle (2θ) range of 16.00° to 16.80° to the maximum peak intensity (B) within a diffraction angle (2θ) range of 17.40° to 18.20° in a diffraction pattern obtained by X-ray diffraction is 1.50 or more and 3.00 or less.

[0010] [ka]

[0011] In the formula, n represents 0 or a positive number.

[0012] The present invention also provides a method for producing a phosphorus compound represented by the following formula (1), comprising the steps of: heating and stirring a phosphorus compound represented by the following formula (1) and an organic solvent which is a good solvent for the phosphorus compound, and dropping an organic solvent which is a poor solvent for the phosphorus compound; a step of dropping an organic solvent that is a poor solvent for the phosphorus compound, followed by filtering under reduced pressure and drying; The present invention relates to a method for producing a crystalline form of a compound represented by the following formula (1):

[0013] [ka]

[0014] In the formula, n represents 0 or a positive number. Effect of the Invention

[0015] According to the present invention, a phosphorus compound having excellent handleability can be provided. [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 is a diagram showing the 1H NMR spectrum of the phosphorus compound produced in Production Example 1. [Diagram 2] FIG. 2 is a diagram showing the 31P NMR spectrum of the phosphorus compound produced in Production Example 1. [Diagram 3] FIG. 3 is a diagram showing the 1H NMR spectrum of the crystalline substance of the phosphorus compound produced in Example 1. [Figure 4] FIG. 4 is a diagram showing the 31P NMR spectrum of the crystalline substance of the phosphorus compound produced in Example 1. [Diagram 5] FIG. 5 is a diagram showing an X-ray diffraction pattern of the crystalline body of the phosphorus compound produced in Example 1. [Figure 6] FIG. 6 is a diagram showing the X-ray diffraction pattern of the phosphorus compound produced in Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The crystal of the phosphorus compound of the present invention will be described below.

[0018] A. Crystals of phosphorus compounds having specific X-ray diffraction patterns The crystalline form of the phosphorus compound of the present invention is represented by the following formula (1), and is characterized in that the ratio (A / B) of the maximum peak intensity (A) within a diffraction angle (2θ) range of 16.00° to 16.80° to the maximum peak intensity (B) within a diffraction angle (2θ) range of 17.40° to 18.20° in a diffraction pattern obtained by X-ray diffraction is 1.50 or more and 3.00 or less.

[0019] [ka]

[0020] In the formula, n represents 0 or a positive number. From the viewpoint of forming a crystal having excellent deliquescence, n is preferably 0 to 1, more preferably 0 to 0.5, even more preferably 0 to 0.3, and most preferably 0 to 0.2. These numbers n represent average values ​​and can be measured by NMR.

[0021] The crystals of the phosphorus compound of the present invention are useful as flame retardants because they have excellent deliquescence and excellent handleability, such as a small angle of repose, etc. Since such crystals of the phosphorus compound do not have deliquescence, when the crystals are blended as a flame retardant in an epoxy resin composition, there is an effect that the bleeding phenomenon does not occur and the physical properties of the cured product do not deteriorate.

[0022] 1. X-ray diffraction pattern In the X-ray diffraction pattern of the crystalline form of the phosphorus compound of the present invention, the ratio (A / B) of the maximum peak intensity (A) within a diffraction angle (2θ) range of 16.00° to 16.80° to the maximum peak intensity (B) within a diffraction angle (2θ) range of 17.40° to 18.20° in the diffraction pattern obtained by X-ray diffraction is 1.50 or more and 3.00 or less. In the present invention, A / B is preferably 1.55 or more and 2.50 or less, more preferably 1.60 or more and 2.00 or less, and even more preferably 1.65 or more and 1.80 or less. It is also preferable that the ratio (C / B) of the maximum peak intensity (C) within a diffraction angle (2θ) range of 10.50° to 10.70° to the maximum peak intensity (B) within a diffraction angle (2θ) range of 17.40° to 18.20° in a diffraction pattern obtained by X-ray diffraction is 0.50 or more and 2.00 or less. In the present invention, C / B is more preferably 0.70 or more and 1.50 or less, even more preferably 0.80 or more and 1.20 or less, and most preferably 0.90 or more and 1.10 or less. It is also preferable that the ratio (D / B) of the maximum peak intensity (D) within a diffraction angle (2θ) range of 13.20° to 13.50° to the maximum peak intensity (B) within a diffraction angle (2θ) range of 17.40° to 18.20° in a diffraction pattern obtained by X-ray diffraction is 0.60 or more and 2.00 or less. In the present invention, D / B is more preferably 0.65 or more and 1.50 or less, even more preferably 0.70 or more and 1.00 or less, and most preferably 0.70 or more and 0.85 or less. It is also preferable that the ratio (E / B) of the maximum peak intensity (E) within a diffraction angle (2θ) range of 15.50° to 15.90° to the maximum peak intensity (B) within a diffraction angle (2θ) range of 17.40° to 18.20° in a diffraction pattern obtained by X-ray diffraction is 0.85 or more and 2.00 or less. In the present invention, E / B is more preferably 0.90 or more and 1.50 or less, even more preferably 0.95 or more and 1.30 or less, and most preferably 1.00 or more and 1.10 or less. It is also preferable that the ratio (F / B) of the maximum peak intensity (F) within a diffraction angle (2θ) range of 20.00 to 21.50° to the maximum peak intensity (B) within a diffraction angle (2θ) range of 17.40° to 18.20° in a diffraction pattern obtained by X-ray diffraction is 0.85 or more and 2.00 or less. In the present invention, F / B is more preferably 0.90 or more and 1.50 or less, even more preferably 0.92 or more and 1.30 or less, and most preferably 0.95 or more and 1.10 or less. Crystals of phosphorus compounds having these maximum peak intensity ratios (A / B, C / B, D / B, E / B and F / B) in their X-ray diffraction patterns are excellent in handleability, for example, by not exhibiting deliquescence and by having a small angle of repose. These maximum peak intensity ratios (A / B, C / B, D / B, E / B and F / B) can be increased or decreased by, for example, recrystallizing the phosphorus compound to increase the crystallinity.

[0023] The X-ray diffraction pattern can be measured by irradiating a powder sample with X-rays and measuring the diffraction intensity of the coherent scattered X-rays produced by forcing the electrons in the material to vibrate at each diffraction angle (2θ). In the present invention, the X-ray diffraction pattern can be measured, for example, using a powder X-ray diffractometer (manufactured by Rigaku Corporation) under the following conditions: output: 3 kW, radiation source: Cu, wavelength: 1.541836 Å, tube voltage: 40 kV, tube current: 40 mA, sampling interval: 0.020°, and scan speed: 4,000° / min.

[0024] 2. Raw phosphorus compounds The method for producing the phosphorus compound represented by formula (1) that is the raw material for the phosphorus compound crystals of the present invention is not particularly limited, but the compound can be produced by reacting bisphenol A with phosphoryl chloride in the presence of a base and a solvent to produce bisphenol A polyphosphate, and then further reacting the bisphenol A polyphosphate with an aqueous methylamine solution.

[0025] Examples of bases used in the production of phosphorus compounds include tertiary amines such as triethylamine, tributylamine, diazabicycloundecene, diazabicyclononene, and 1,4-diazabicyclo[2.2.2]octane; pyridines such as pyridine and N,N-dimethylaminopyridine; imidazoles such as 1-methylimidazole; and phosphines such as triphenylphosphine, tributylphosphine, and tricyclohexylphosphine.

[0026] Examples of solvents used in the production of phosphorus compounds include ketones such as methyl ethyl ketone, methyl amyl ketone, diethyl ketone, acetone, methyl isopropyl ketone, propylene glycol monomethyl ether acetate, cyclohexanone, etc.; ethers such as tetrahydrofuran, 1,2-dimethoxyethane, 1,2-diethoxyethane, propylene glycol monomethyl ether, etc.; esters such as ethyl acetate, n-butyl acetate, etc.; aromatic hydrocarbons such as benzene, toluene, xylene, etc.; halogenated aliphatic hydrocarbons such as carbon tetrachloride, chloroform, trichloroethylene, methylene chloride, etc.; and halogenated aromatic hydrocarbons such as chlorobenzene, etc.

[0027] The above reaction can be carried out at -80°C to 100°C, preferably room temperature to 50°C, for 0.5 to 72 hours, preferably 1 to 24 hours.

[0028] 3. Other characteristics of phosphorus compound crystals The average particle size (D50) of the crystals of the phosphorus compound of the present invention is preferably 0.1 μm to 500 μm, more preferably 1 μm to 300 μm, even more preferably 10 μm to 200 μm, and most preferably 30 μm to 100 μm. When the average particle size is within the above range, no aggregation of particles occurs, and the flowability is good when blended into an epoxy resin composition. The maximum particle size of the crystals of the phosphorus compound of the present invention is preferably 50 μm to 1000 μm, more preferably 80 μm to 800 μm, even more preferably 100 μm to 500 μm, and most preferably 150 μm to 300 μm. The maximum particle size in the above range is preferable because it has good solubility in solvents and the like. The average particle size (D50) and maximum particle size of the phosphorus compound crystals can be measured by a laser diffraction scattering method using a particle size measuring device (LA-950V2, manufactured by Horiba, Ltd.) by dispersing the phosphorus compound crystals to be measured in a mixture of heptane and a nonionic surfactant (Newcol (registered trademark) 80 manufactured by Nippon Nyukazai Co., Ltd.).

[0029] The melting point of the crystals of the phosphorus compound of the present invention is preferably from 10° C. to less than 300° C., more preferably from 50° C. to 250° C., and even more preferably from 100° C. to 200° C. When the melting point is in the above range, the crystals are not sticky and have excellent workability. The melting point of the phosphorus compound crystal is determined by measurement using a differential scanning calorimeter, and is the temperature of the endothermic peak top observed when the phosphorus compound crystal is heated from 25°C at a rate of 10°C / min in a nitrogen atmosphere.

[0030] The thermal weight loss of the crystal of the phosphorus compound of the present invention is preferably 0.5% by mass to 3.0% by mass, more preferably 0.8% by mass to 2.0% by mass, and even more preferably 1.0% by mass to 1.5% by mass. It is believed that a crystal of the phosphorus compound with higher purity can be obtained by having the thermal weight loss in the above range. The thermal weight loss of a phosphorus compound crystal can be determined by using a thermogravimetric differential thermal analyzer TG / DTA7200 (manufactured by SII NanoTechnology Inc.) to raise the temperature from 30°C to 140°C at a rate of 10°C / min in a nitrogen atmosphere, and measuring the weight loss two hours after reaching 140°C.

[0031] The angle of repose of the crystals of the phosphorus compound of the present invention is preferably 60° or less, more preferably 50° or less, and even more preferably 45° or less. When the angle of repose is as described above, the fluidity is good, and the crystals are easily removed from a reaction tank and transported, resulting in good workability during production. The angle of repose can be measured by injecting and depositing crystals of the phosphorus compound onto a disk using a funnel, and measuring the angle at which the crystals remain stable without spontaneously collapsing as the angle of repose (°).

[0032] The crystals of the phosphorus compound of the present invention are easy to handle, and when incorporated into a curable resin composition mainly composed of an epoxy resin, they have good cured physical properties and can impart flame retardancy, making them suitable for use as a flame retardant for epoxy resins.

[0033] B. Method for producing crystals of phosphorus compound having a specific X-ray diffraction pattern Next, a method for producing the crystal of the phosphorus compound of the present invention having a specific X-ray diffraction pattern will be described. The crystal of the phosphorus compound of the present invention can be obtained by changing the crystal structure of the phosphorus compound represented by formula (1) that serves as a raw material. The method for obtaining the crystal structure is not particularly limited, but examples thereof include a method having the following steps:

[0034] 1. A step of mixing a phosphorus compound represented by formula (1) with a good solvent The method for mixing the phosphorus compound represented by formula (1) with the organic solvent that is a good solvent for the phosphorus compound is not particularly limited, but is preferably a method that can obtain a homogeneous mixture. For example, a homogeneous mixture can be easily obtained by heating and stirring the phosphorus compound and the good solvent.

[0035] The good solvent may be any solvent capable of dissolving the phosphorus compound. From the viewpoint of easily obtaining a highly pure crystal of the phosphorus compound having a specific X-ray diffraction pattern, the good solvent is preferably capable of dissolving 100 parts by mass or more of the phosphorus compound in 100 parts by mass of the organic solvent at 85° C., and more preferably capable of dissolving 1000 parts by mass or more of the phosphorus compound. As such good solvents, alcohol-based solvents, halogen-based solvents and amide-based solvents are preferred, alcohol-based solvents and amide-based solvents are more preferred, and alcohol-based solvents are even more preferred. As the alcohol-based solvent, aliphatic alcohols having 1 to 7 carbon atoms, such as methanol, ethanol, isopropanol, isobutanol, and 2-propanol, and alicyclic alcohols having 5 to 7 carbon atoms, such as cyclopentanol, cyclohexanol, and cycloheptanol, are preferred. Among these, it is preferred to use methanol as the good solvent, from the viewpoint that a crystal of a phosphorus compound having a specific X-ray diffraction pattern can be easily obtained with high purity.

[0036] Here, the amount of the good solvent used is preferably 0.05 to 1.0 times, more preferably 0.07 to 0.7 times, and even more preferably 0.1 to 0.6 times, by volume, relative to the phosphorus compound. The stirring temperature is preferably 40° C. to 98° C., more preferably 60° C. to 95° C., and even more preferably 80° C. to 90° C. By keeping the amount and temperature within the above ranges, a homogeneous mixture is easily obtained.

[0037] 2. Dropping a poor solvent into the mixture The method for adding the organic solvent, which is a poor solvent for the phosphorus compound, dropwise to the mixture obtained in the above step is not particularly limited, but a method in which the poor solvent is added dropwise while the phosphorus compound and the good solvent are heated and stirred is preferred. From the viewpoint of easily obtaining a highly pure crystal of the phosphorus compound having a specific X-ray diffraction pattern, the amount of the poor solvent used is preferably 0.5 to 10 times, more preferably 1.0 to 8 times, and even more preferably 1.5 to 5.0 times the total amount of the phosphorus compound and the good solvent, based on mass; the dropwise addition time is preferably 5 to 120 minutes, more preferably 8 to 80 minutes, and even more preferably 10 to 60 minutes; the dropwise addition rate is preferably 100 g / hour to 1000 g / hour, more preferably 200 g / hour to 600 g / hour, and even more preferably 300 g / hour to 500 g / hour; and the temperature during dropwise addition is preferably 40° C. or higher and 130° C. or lower, more preferably 50° C. or higher and 120° C. or lower, and even more preferably 70° C. or higher and 100° C. or lower.

[0038] The poor solvent may be any solvent that does not dissolve the phosphorus compound. From the viewpoint that the crystal of the phosphorus compound having a specific X-ray diffraction pattern can be easily obtained with high purity, it is preferable that the poor solvent cannot dissolve 100 parts by mass or more of the phosphorus compound with respect to 100 parts by mass of the organic solvent at 25°C, more preferably that the poor solvent cannot dissolve 10 parts by mass or more of the phosphorus compound, and even more preferably that the poor solvent cannot dissolve 1 part by mass or more of the phosphorus compound. In addition, it is preferable that the poor solvent cannot dissolve 100 parts by mass or more of the phosphorus compound in the presence of 5 parts by mass of the good solvent with respect to 100 parts by mass of the organic solvent at 25°C, more preferably that the poor solvent cannot dissolve 50 parts by mass or more of the phosphorus compound, and even more preferably that the poor solvent cannot dissolve 10 parts by mass or more of the phosphorus compound. As such a poor solvent, from the viewpoint of facilitating the production of high-purity crystals of a phosphorus compound having a specific X-ray diffraction pattern, aliphatic hydrocarbon solvents, aromatic hydrocarbon solvents, ether solvents, ketone solvents and ester solvents are preferred, ketone solvents and ester solvents are more preferred, and ketone solvents are even more preferred. As the ketone solvent, a compound having 3 to 15 carbon atoms can be used, and examples thereof include aliphatic ketone solvents such as methyl ethyl ketone, methyl isopropyl ketone, acetone, butanone, pentanone, acetylacetone, methyl butyl ketone, and methyl isobutyl ketone, and cyclic ketone solvents such as cyclopropanone, cyclohexanone, isophorone, and N-methylpyrrolidone. Among these, it is preferable to use an aliphatic ketone solvent as the poor solvent, from the viewpoint of easily obtaining a highly pure crystal of the phosphorus compound having a specific X-ray diffraction pattern. In the present invention, from the viewpoint of easily obtaining a highly pure crystal of a phosphorus compound having a specific X-ray diffraction pattern, the poor solvent is preferably a ketone solvent having 3 to 10 carbon atoms, more preferably a ketone solvent having 4 to 8 carbon atoms, even more preferably a ketone solvent having 4 to 7 carbon atoms, and most preferably methyl isobutyl ketone and methyl ethyl ketone. Examples of the ester solvent include alkyl acetates such as ethyl acetate, propyl acetate, and butyl acetate, and glycol ester solvents such as ethylene glycol monomethyl ether acetate. Among these, alkyl acetates are preferred, and propyl acetate and butyl acetate are more preferred, from the viewpoint of facilitating the production of highly pure crystals of a phosphorus compound having a specific X-ray diffraction pattern.

[0039] 3. Drying process The mixture obtained in the above step is dried to obtain a crystal of the phosphorus compound. The drying method is not particularly limited, but it is preferable to drop an organic solvent, which is a poor solvent, and then perform vacuum filtration and drying. By carrying out this drying method, a crystal of the phosphorus compound having a specific X-ray diffraction pattern can be easily obtained with high purity.

[0040] 4.Other processes The production method of the present invention includes a step of dropping a poor solvent while heating and stirring a phosphorus compound and a good solvent, and a step of drying the poor solvent after dropping the poor solvent, but may include other steps as necessary. Examples of the other steps include (1) a step of synthesizing a phosphorus compound, and (2) a step of cooling the mixture after a step of dropping a poor solvent into the mixture.

[0041] (1) A process for synthesizing phosphorus compounds The process for synthesizing the phosphorus compound can be the same as that described in the section "2. Raw material phosphorus compound" of "A. Crystal of phosphorus compound having a specific X-ray diffraction pattern".

[0042] (2) cooling the mixture after the step of dropping the poor solvent into the mixture The mixture is preferably cooled by controlling the cooling rate while stirring the mixture, preferably from 0.1° C. / min to 5° C. / min, more preferably from 0.2° C. / min to 3° C. / min, even more preferably from 0.3° C. / min to 1° C. / min, and even more preferably from 0.4° C. / min to 0.8° C. / min. The mixture is cooled preferably to 10° C. to 30° C., more preferably to 15° C. to 28° C., and after cooling, it is preferable to further stir for 30 minutes to 2 hours. By carrying out these operations, rapid progress of crystallization can be suppressed, and a phosphorus compound with higher crystallinity can be obtained.

[0043] C. Curable resin composition The crystals of the phosphorus compound of the present invention can be combined with an epoxy resin, a curing agent, etc. to form a curable resin composition having excellent flame retardancy.

[0044] The content of the phosphorus compound crystals of the present invention in the curable resin composition of the present invention is not particularly limited, but is preferably 0.01 to 10 parts by mass, more preferably 0.05 to 5 parts by mass, relative to 100 parts by mass of the epoxy resin and the curing agent in total. The content of the phosphorus compound crystals is preferably an amount such that the phosphorus content in the curable resin composition is 0.1 to 5% by mass, more preferably 0.5 to 3% by mass. By using the phosphorus compound crystals in the above range, the flame retardancy of the curable resin composition is further improved.

[0045] 1. Epoxy Resin The epoxy resin may be any resin having at least two epoxy groups in the molecule, and may be used without any particular limitations on the molecular structure, molecular weight, etc.

[0046] Examples of epoxy resins include polyglycidyl ethers of mononuclear polyhydric phenol compounds such as hydroquinone, resorcinol, pyrocatechol, and phloroglucinol; polynuclear polyphenols such as dihydroxynaphthalene, biphenol, methylene bisphenol (bisphenol F), methylene bis(ortho-cresol), ethylidene bisphenol, isopropylidene bisphenol (bisphenol A), isopropylidene bis(ortho-cresol), tetrabromo bisphenol A, 1,3-bis(4-hydroxycumylbenzene), 1,4-bis(4-hydroxycumylbenzene), 1,1,3-tris(4-hydroxyphenyl)butane, 1,1,2,2-tetra(4-hydroxyphenyl)ethane, thiobisphenol, sulfobisphenol, oxybisphenol, phenol novolac, orthocresol novolac, ethylphenol novolac, butylphenol novolac, octylphenol novolac, resorcinol novolac, and terpene phenol. polyglycidyl ethers of polyhydric phenol compounds; polyglycidyl ethers of polyhydric alcohol compounds such as ethylene glycol, propylene glycol, butylene glycol, hexanediol, polyethylene glycol, polypropylene glycol, thioglycol, dicyclopentadiene dimethanol, 2,2-bis(4-hydroxycyclohexyl)propane (hydrogenated bisphenol A), glycerin, trimethylolpropane, pentaerythritol, sorbitol and bisphenol A-alkylene oxide adducts; glycidyl esters of aliphatic, aromatic or alicyclic polybasic acids such as maleic acid, fumaric acid, itaconic acid, succinic acid, glutaric acid, suberic acid, adipic acid, azelaic acid, sebacic acid, dimer acid, trimer acid, phthalic acid, isophthalic acid, terephthalic acid, trimellitic acid, trimesic acid, pyromellitic acid, tetrahydrophthalic acid and endomethylenetetrahydrophthalic acid, and homopolymers or copolymers of glycidyl methacrylate;Epoxy compounds having a glycidylamino group, such as N,N-diglycidylaniline, bis(4-(N-methyl-N-glycidylamino)phenyl)methane, diglycidyl orthotoluidine, N,N-bis(2,3-epoxypropyl)-4-(2,3-epoxypropoxy)-2-methylaniline, N,N-bis(2,3-epoxypropyl)-4-(2,3-epoxypropoxy)aniline and N,N,N',N'-tetra(2,3-epoxypropyl)-4,4-diaminodiphenylmethane; vinylcyclohexene diepoxide, Examples of the epoxy resin include cyclopentanediene diepoxide, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, 3,4-epoxy-6-methylcyclohexylmethyl-6-methylcyclohexanecarboxylate, and bis(3,4-epoxy-6-methylcyclohexylmethyl)adipate and other epoxidized cyclic olefin compounds; epoxidized conjugated diene polymers such as epoxidized polybutadiene and epoxidized styrene-butadiene copolymers; and heterocyclic compounds such as triglycidyl isocyanurate. These epoxy resins can also be used in a form in which they are internally crosslinked with a prepolymer of terminal isocyanate, or in a form in which they are polymerized with a polyvalent active hydrogen compound (polyhydric phenol, polyamine, carbonyl group-containing compound, polyphosphate ester, etc.). The epoxy resins may be used alone or in combination of two or more kinds.

[0047] 2.Reactive diluents In the curable resin composition of the present invention, a reactive diluent can be used together with the epoxy resin in order to adjust the viscosity of the curable resin composition to a desired level. As such a reactive diluent, it is preferable to use a diluent having at least one epoxy group in the molecule, from the viewpoint of suppressing a decrease in the heat resistance and glass transition temperature of the cured product when the epoxy resin composition is cured.

[0048] The number of epoxy groups contained in the reactive diluent may be one or may be two or more, and is not particularly limited. Examples of reactive diluents having one epoxy group include n-butyl glycidyl ether, C12-C14 alkyl glycidyl ether, allyl glycidyl ether, 2-ethylhexyl glycidyl ether, styrene oxide, phenyl glycidyl ether, cresyl glycidyl ether, p-sec-butylphenyl glycidyl ether, t-butylphenyl glycidyl ether, glycidyl methacrylate, and tertiary carboxylic acid glycidyl ester. Examples of reactive diluents having two epoxy groups include ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, and neopentyl glycol diglycidyl ether. Examples of reactive diluents having three epoxy groups include trimethylolpropane triglycidyl ether and glycerin triglycidyl ether.

[0049] The amount of reactive diluent blended with respect to the epoxy resin is not particularly limited, but may be selected depending on the intended use. Usually, it is preferable to blend 3 to 50 parts by mass of reactive diluent with respect to 100 parts by mass of epoxy resin.

[0050] 3. Hardener Examples of the curing agent include an acid anhydride-based curing agent, a phenol-based curing agent, an amine-based curing agent, a polythiol-based curing agent, and an imidazole-based curing agent.

[0051] Examples of acid anhydride curing agents include himic anhydride, phthalic anhydride, maleic anhydride, methyl himic anhydride, succinic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, trialkyltetrahydrophthalic anhydride-maleic anhydride adduct, benzophenonetetracarboxylic anhydride, trimellitic anhydride, pyromellitic anhydride, and hydrogenated methylnadic anhydride.

[0052] Examples of the phenol-based curing agent include polyhydric phenol compounds such as phenol novolak resin, cresol novolak resin, aromatic hydrocarbon formaldehyde resin-modified phenol resin, dicyclopentadiene phenol addition type resin, phenol aralkyl resin (Xylok resin), naphthol aralkyl resin, trisphenylol methane resin, tetraphenylol ethane resin, naphthol novolak resin, naphthol-phenol co-condensed novolak resin, naphthol-cresol co-condensed novolak resin, biphenyl-modified phenol resin (a polyhydric phenol compound in which a phenol nucleus is linked by a bismethylene group), biphenyl-modified naphthol resin (a polyhydric naphthol compound in which a phenol nucleus is linked by a bismethylene group), aminotriazine-modified phenol resin (a compound having a phenol skeleton, a triazine ring, and a primary amino group in its molecular structure), and alkoxy group-containing aromatic ring-modified novolak resin (a polyhydric phenol compound in which a phenol nucleus and an alkoxy group-containing aromatic ring are linked by formaldehyde).

[0053] Examples of the amine-based curing agent include alkylene diamines such as ethylenediamine, 1,2-diaminopropane, 1,3-diaminopropane, 1,3-diaminobutane, 1,4-diaminobutane, hexamethylenediamine, and metaxylenediamine; polyalkyl polyamines such as diethylenetriamine, triethylenetriamine, and tetraethylenepentamine; 1,4-diaminocyclohexane, 1,3-diaminocyclohexane, 1,3-diaminomethylcyclohexane, 1,2-diaminocyclohexane, 1,4-diamino-3,6-diethylcyclohexane, 4,4'-diaminodicyclohexylmethane, 1,3-bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, 4,4 alicyclic polyamines such as 4-aminocyclohexylpropane, bis(4-aminocyclohexyl)sulfone, 4,4'-diaminodicyclohexyl ether, 2,2'-dimethyl-4,4'-diaminodicyclohexylmethane, isophorone diamine, and norbornene diamine; aromatic polyamines such as diaminodiphenylmethane, diaminodiphenylsulfone, diethyltoluenediamine, 1-methyl-3,5-diethyl-2,4-diaminobenzene, 1-methyl-3,5-diethyl-2,6-diaminobenzene, 1,3,5-triethyl-2,6-diaminobenzene, 3,3'-diethyl-4,4'-diaminodiphenylmethane, and 3,5,3',5'-tetramethyl-4,4'-diaminodiphenylmethane;N,N-dimethylaminoethylamine, N,N-diethylaminoethylamine, N,N-diisopropylaminoethylamine, N,N-diallylaminoethylamine, N,N-benzylmethylaminoethylamine, N,N-dibenzylaminoethylamine, N,N-cyclohexylmethylaminoethylamine, N,N-dicyclohexylaminoethylamine, N-(2-aminoethyl)pyrrolidine, N-(2-aminoethyl)piperidine, N-(2-aminoethyl)morpholine, N-(2-aminoethyl)piperazine, N-(2-aminoethyl)-N'-methylpiperazine, N,N-dimethylaminopropylamine, N,N-diethylaminopropylamine, N,N-diisopropylaminopropylamine, N,N-diallylaminopropylamine, N,N-benzylmethylaminopropylamine, N,N-dibenzylaminopropylamine, N,N-Cyclohexylmethylaminopropylamine, N,N-Dicyclohexylaminopropylamine, N-(3-aminopropyl)pyrrolidine, N-(3-aminopropyl)piperidine, N-(3-aminopropyl)morpholine, N-(3-aminopropyl)piperazine, N-(3-aminopropyl)-N'-methylpiperidine, 4-(N,N-Dimethylamino)benzylamine, 4-(N,N-Diethylamino)benzylamine, 4-(N,N-Diisopropylamino)benzylamine, N,N,-Dimethylisophoronediamine, N,N-Dimethylbisaminocyclohexane, N,N,N'-Trimethylethylenediamine, N'-Ethyl-N,N-Dimethylethylenediamine, N,N,N'-Triethylethylenediamine, N'-Ethyl-N,N-Dimethylpropanediamine, N'-Ethyl-N,N-Dibenzylaminopropylamine;N,N-(bisaminopropyl)-N-methylamine, N,N-bisaminopropylethylamine, N,N-bisaminopropylpropylamine, N,N-bisaminopropylbutylamine, N,N-bisaminopropylpentylamine, N,N-bisaminopropylhexylamine, N,N-bisaminopropyl-2-ethylhexylamine, N,N-bisaminopropylcyclohexylamine, N,N-bisaminopropylbenzylamine, N,N-bisaminopropylallylamine, bis[3-(N,N-dimethylaminopropyl)]amine, bis [3-(N,N-diethylaminopropyl)]amine, bis[3-(N,N-diisopropylaminopropyl)]amine, bis[3-(N,N-dibutylaminopropyl)]amine; dibasic acid dihydrazides such as oxalic acid dihydrazide, malonic acid dihydrazide, succinic acid dihydrazide, glutaric acid dihydrazide, adipic acid dihydrazide, suberic acid dihydrazide, azelaic acid dihydrazide, sebacic acid dihydrazide, and phthalic acid dihydrazide; guanidine compounds such as dicyandiamide, benzoguanamine, and acetoguanamine; melamine, etc.;

[0054] Modified amine-based curing agents obtained by modifying amines can also be used. Modification methods include dehydration condensation with carboxylic acid, addition reaction with epoxy resin, addition reaction with isocyanate, Michael addition reaction, Mannich reaction, condensation reaction with urea, and condensation reaction with ketone. Examples of carboxylic acids that can be used to modify amines include aliphatic, aromatic, or alicyclic polybasic acids such as maleic acid, fumaric acid, itaconic acid, succinic acid, glutaric acid, suberic acid, adipic acid, azelaic acid, sebacic acid, dimer acid, trimer acid, phthalic acid, isophthalic acid, terephthalic acid, trimellitic acid, trimesic acid, pyromellitic acid, tetrahydrophthalic acid, hexahydrophthalic acid, and endomethylenetetrahydrophthalic acid.

[0055] Examples of epoxy compounds that can be used to modify amines include the epoxy compounds exemplified above as the epoxy resin that is component (B).

[0056] Examples of isocyanate compounds that can be used to modify amines include aromatic diisocyanates such as 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, diphenylmethane-4,4'-diisocyanate, phenylene diisocyanate, xylylene diisocyanate, tetramethylxylylene diisocyanate, 1,5-naphthylene diisocyanate, 1,5-tetrahydronaphthalene diisocyanate, 3,3'-dimethyldiphenyl-4,4'-diisocyanate, dianisidine diisocyanate, and tetramethylxylylene diisocyanate; isophorone diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, and the like. Examples of the isocyanate compounds include alicyclic diisocyanates such as cyclohexane, trans-1,4-cyclohexyl diisocyanate, and norbornene diisocyanate; aliphatic diisocyanates such as tetramethylene diisocyanate, 1,6-hexamethylene diisocyanate, 2,2,4 and / or (2,4,4)-trimethylhexamethylene diisocyanate, and lysine diisocyanate; isocyanurate trimerization products, biuret trimerization products, and trimethylolpropane adducts of the above-listed diisocyanates; triphenylmethane triisocyanate, 1-methylbenzene-2,4,6-triisocyanate, and dimethyltriphenylmethane tetraisocyanate. Furthermore, these isocyanate compounds can be used in the form of modified products such as carbodiimide modified, isocyanurate modified, and biuret modified, or in the form of blocked isocyanates blocked with various blocking agents.

[0057] Examples of polythiol-based curing agents include pentaerythritol tetrakis(3-mercaptopropionate), pentaerythritol tetrakis(thioglycolate), dipentaerythritol hexakis(3-mercaptopropionate), and dipentaerythritol. Examples of such mercaptoalkyl groups include hexakis(3-mercaptobutyrate), 1,3,4,6-tetrakis(2-mercaptoethyl)-1,3,4,6-tetraazaochydropentalene-2,5-dione, 1,3,5-tris(3-mercaptopropyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 4-mercaptomethyl-1,8-dimercapto-3,6-dithiaoctane, 4,8-, 4,7-, or 5,7-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, and 1,3,4,6-tetrakis(2-mercaptoethyl)glycoluril.

[0058] Examples of the imidazole-based curing agent include 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-isopropylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 2-aminopropylimidazole, 1-phenylmethyl-2-imidazole, 1-phenylmethyl-2-ethyl-4-methylimidazole, 1-phenylmethyl-2-phenylimidazole, 1-butoxycarbonylethyl-2-methylimidazole, and 1-butoxycarbonylethyl-2-methylimidazole. Carbonylethyl-2-ethyl-4-methylimidazole, 1-butoxycarbonylethyl-2-phenylimidazole, 1-(2-ethylhexyl)carbonylethyl-2-methylimidazole, 1-(2-ethylhexyl)carbonylethyl-2-ethyl-4-methylimidazole, 1-(2-ethylhexyl)carbonylethyl-2-phenylimidazole, 1-octyloxycarbonylethyl-2-methylimidazole, 1-octyloxycarbonylethyl-2-ethyl-4-methylimidazole, 1-octyloxycarbonylethyl ethyl-2-phenylimidazole, hexanediol bis(2-methylimidazolyl ethanoate) ester, hexanediol bis(2-ethyl-4-methylimidazolyl ethanoate) ester, hexanediol bis(2-phenylimidazolyl ethanoate) ester, decanediol bis(2-methylimidazolyl ethanoate) ester, decanediol bis(2-ethyl-4-methylimidazolyl ethanoate) ester, decanediol bis(2-phenylimidazolyl ethanoate) ester, tricyclopentane dimethanol bis(2 1-(2-hydroxynaphthylmethyl)-2-methylimidazole, 1-(2-hydroxynaphthylmethyl)-2-ethyl-4-methylimidazole, 1-(2-hydroxynaphthylmethyl)-2-phenylimidazole, and imidazole silane (for example, 2MUSIZ manufactured by Shikoku Chemical Industry Co., Ltd.).These may also be used in the form of a salt with trimellitic acid, isocyanuric acid, boron, etc. Furthermore, these imidazole compounds may also be modified to form modified imidazole curing agents in the same manner as the above-mentioned modified amine curing agents.

[0059] Examples of commercially available hardeners include ADEKA HARDENER (registered trademark) EH-3636AS, ADEKA HARDENER (registered trademark) EH-4351S (manufactured by ADEKA Corporation; dicyandiamide-type latent hardener), ADEKA HARDENER (registered trademark) EH-5011S, ADEKA HARDENER (registered trademark) EH-5046S (manufactured by ADEKA Corporation; imidazole-type latent hardener), ADEKA HARDENER (registered trademark) EH-4357S, and ADEKA HARDENER (registered trademark). (registered trademark) EH-5057P, ADEKA HARDNER (registered trademark) EH-5057PK (manufactured by ADEKA Corporation; polyamine-type latent curing agent), Amicure (registered trademark) PN-23, Amicure (registered trademark) PN-40 (manufactured by Ajinomoto Fine Techno; amine adduct-based latent curing agent), Amicure (registered trademark) VDH (manufactured by Ajinomoto Fine Techno; hydrazide-based latent curing agent), Fujicure (registered trademark) FXR-1020 (manufactured by T&K TOKA Corporation; latent curing agent), Curesol (registered trademark) (manufactured by Shikoku Chemical Industry Co., Ltd.; imidazole-based curing agent), TS-G (manufactured by Shikoku Chemical Industry Co., Ltd.; polythiol-based curing agent), DPMP, PEMP (manufactured by SC Organic Chemical Co., Ltd.; polythiol-based curing agent), and PETG (manufactured by Yodo Chemical Co., Ltd.; polythiol-based curing agent) are listed. These curing agents may be used alone or in combination of two or more.

[0060] The amount of the curing agent is not particularly limited, but is preferably 1 to 70 parts by mass, more preferably 1 to 50 parts by mass, and even more preferably 3 to 30 parts by mass, relative to 100 parts by mass of the epoxy resin.

[0061] 4. Curing accelerator In the present invention, the above curing agent can be used in combination with a known curing accelerator for epoxy resins as necessary. Examples of the curing accelerator include phosphines such as triphenylphosphine; phosphonium salts such as tetraphenylphosphonium bromide; amines such as benzyldimethylamine and 2,4,6-tris(dimethylaminomethyl)phenol; quaternary ammonium salts such as trimethylammonium chloride; ureas such as 3-(p-chlorophenyl)-1,1-dimethylurea, 3-(3,4-dichlorophenyl)-1,1-dimethylurea, 3-phenyl-1,1-dimethylurea, isophorone diisocyanate-dimethylurea, and tolylene diisocyanate-dimethylurea; complexes of boron trifluoride and amines, and complexes of boron trifluoride and ether compounds. These curing accelerators may be used alone or in combination of two or more. The amount of the curing accelerator is not particularly limited and can be appropriately set depending on the application of the curable resin composition.

[0062] 5. Other flame retardants The curable resin composition of the present invention may contain other flame retardants, such as at least one flame retardant selected from the group consisting of phosphorus compounds other than the crystals of the phosphorus compound of the present invention, nitrogen compounds, boron compounds, halogen compounds, silicon compounds, and inorganic compounds.

[0063] Examples of phosphorus compounds other than the crystals of the phosphorus compound of the present invention include aliphatic phosphoric acid esters such as trimethyl phosphate, triethyl phosphate, tributyl phosphate, trioctyl phosphate, and tributoxyethyl phosphate; aromatic phosphoric acid esters such as triphenyl phosphate, cresyl diphenyl phosphate, dicresyl phenyl phosphate, tricresyl phosphate, trixylenyl phosphate, xylenyl diphenyl phosphate, tris(isopropylphenyl)phosphate, isopropylphenyl diphenyl phosphate, bis(isopropylphenyl)phenyl phosphate, tris(trimethylphenyl)phosphate, tris(t-butylphenyl)phosphate, hydroxyphenyl diphenyl phosphate, and octyl diphenyl phosphate; resorcinol polyphenyl phosphate, 1,3-phenylene bis(2,6-dimethylphenyl phosphate), resorcinol poly(di-2,6-xylyl)phosphate, bisphenol A polycresyl phosphate, and hydroquinone poly( 2,6-xylyl)phosphate and condensates thereof; phosphates such as ammonium phosphate and melamine phosphate; condensed phosphates such as ammonium polyphosphate and melamine polyphosphate; aluminum tris(diethylphosphinate), aluminum tris(methylethylphosphinate), zinc bis(diethylphosphinate), zinc bis(methylethylphosphinate), zinc bis(diphenylphosphinate), zinc triphosphinate, titanyl bis(diethylphosphinate), tetrakis(diethylphosphinate), metal salts of phosphinic acid such as titanium bis(methylethylphosphinate), titanyl bis(methylethylphosphinate), titanium tetrakis(diphenylphosphinate), and titanyl tetraphosphinate; phosphinic acid esters such as phenyl diphenylphosphinate, methyl diphenylphosphinate, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (hereinafter referred to as DOPO), and 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide;Examples of such compounds include DOPO-modified compounds such as addition reaction products of DOPO and acrylic esters, addition reaction products of DOPO and epoxy resins, and addition reaction products of HCA and hydroquinone; phosphine oxide compounds such as diphenylvinylphosphine oxide, triphenylphosphine oxide, trialkylphosphine oxide, and tris(hydroxyalkyl)phosphine oxide; phosphazene derivatives such as hexacyclotriphosphazene and hexaphenylcyclotriphosphazene; and red phosphorus.

[0064] Among these phosphorus compounds, ammonium polyphosphate, melamine polyphosphate, aluminum tris(diethylphosphinate), 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (HCA), 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (HCA-HQ manufactured by Sanko Co., Ltd.), hexaphenylcyclotriphosphazene, or a flame retardant represented by any one of the following formulas (6-1) to (6-11) is more preferred.

[0065] [ka]

[0066] [ka]

[0067] [ka]

[0068] [ka]

[0069] [ka]

[0070] In the formula (6-1), s represents an integer of 1 to 50. In formulas (6-3) to (6-5), a, b and c each independently represent an integer of 1 to 5. In formulae (6-6) and (6-7), d and e each independently represent an integer of 1 to 10. In the formula (6-8), f represents an integer of 1 to 50. In formula (6-11), A is a hydrogen atom or -OR 17 R 17 R represents an alkyl group having 1 to 6 carbon atoms. 17 Examples of the alkyl group having 1 to 6 carbon atoms represented by the formula (I) include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a secondary butyl group, a tertiary butyl group, a pentyl group, and a hexyl group.

[0071] Among the above phosphorus compounds, tris(diethylphosphinate)aluminum and 10-(2,5-phosphaphenanthrene-10-oxide are particularly preferred because of their excellent flame retardant effect.

[0072] Examples of the nitrogen compound include silicon nitride, aluminum nitride, and compounds that form salts of a triazine compound with cyanuric acid or isocyanuric acid. The salts of a triazine compound with cyanuric acid or isocyanuric acid are adducts of a triazine compound with cyanuric acid or isocyanuric acid, and are usually adducts having a molar ratio of 1:1, and sometimes 2:1. Among the triazine compounds, those that do not form salts with cyanuric acid or isocyanuric acid are excluded.

[0073] Examples of the triazine compounds include melamine, mono(hydroxymethyl)melamine, di(hydroxymethyl)melamine, tri(hydroxymethyl)melamine, benzoguanamine, acetoguanamine, and 2-amido-4,6-diamino-1,3,5-triazine.

[0074] Examples of the boron compound include boric acid (orthoboric acid, metaboric acid, etc.), borate (alkali metal borates such as sodium tetraborate, alkaline earth metal salts such as barium metaborate, transition metal salts such as zinc borate, etc.), condensed boric acid (salts) (pyroboric acid, tetraboric acid, pentaboric acid, octaboric acid, or metal salts thereof, etc.), boron nitride, etc. These boron-containing compounds may be hydrated (e.g., borax, which is hydrated sodium tetraborate, etc.). These boron compounds may be used alone or in combination of two or more.

[0075] Examples of the halogen compounds include tetrabromobisphenol A, carbonate oligomers of tetrabromobisphenol A, tetrabromobisphenol A bis(2,3-dibromopropyl ether), tetrabromobisphenol A bis(2-bromoethyl ether), and tetrabromobisphenol A derivatives such as tetrabromobisphenol A diglycidyl ether and brominated bisphenol adducts; decabromodiphenyl ether, octabromodiphenyl ether, ethylene bistetrabromophthalimide, hexabromocyclododecane, 1,2-bis(pentabromophenyl)ethane, 2,3-dibromopropyl pentabromophenyl ether, 1,2-bis(2,4,6-tribromophenoxy)ethane, 2,4,6-tribromophenyl ether, 2,3-dibromopropyl penta ... Examples of the brominated aromatic compounds include brominated aromatic compounds such as thris(2,4,6-tribromophenoxy)-1,3,5-triazine, brominated polystyrene, polybrominated styrene, and pentabromobenzyl acrylate (monomer); chlorinated paraffins; chlorinated naphthalenes; and halogen-based phosphate esters such as tris(chloroethyl)phosphate, tris(2,3-dichloropropyl)phosphate, tris(bromochloropropyl)phosphate, tris(2,3-dibromopropyl)phosphate, tris(bromochlorophenyl)phosphate, 2,3-dibromopropyl-2,3-dichloropropyl phosphate, tris(tribromophenyl)phosphate, tris(dibromophenyl)phosphate, and tris(tribromoneopentyl)phosphate.

[0076] Examples of the inorganic compound include antimony trioxide, antimony pentoxide, aluminum hydroxide, magnesium hydroxide, boehmite, and graphite.

[0077] Examples of commercially available flame retardants include phosphate esters (e.g., PN-600 and PFR manufactured by ADEKA CORPORATION), phosphorus-containing phenoxy resins (e.g., PhenoTohto ERF-001M30 and TX-0924K30 manufactured by Nippon Steel Chemical Co., Ltd.), hydroxyl-containing phosphate esters (e.g., DAIGUARD-580 and DAIGUARD-610 manufactured by Daihachi Chemical Industry Co., Ltd.), HCA derivatives (e.g., HCA-HQ, M-Ester, and ME-P8 manufactured by Sanko Co., Ltd.), and intumescent flame retardants, which are composite flame retardants (e.g., FP-2100JC, FP-2200S, and FP-2500S manufactured by ADEKA CORPORATION).

[0078] The content of the other flame retardant is preferably 1 part by mass to 1,000 parts by mass, more preferably 20 parts by mass to 200 parts by mass, and even more preferably 50 parts by mass to 150 parts by mass, relative to 100 parts by mass of the crystalline form of the phosphorus compound of the present invention.

[0079] When the other flame retardant contains phosphorus atoms, the content of the other flame retardant is preferably 0.1% by mass to 5% by mass, more preferably 0.5% by mass to 3% by mass, based on the total mass of the epoxy resin, curing agent, crystals of the phosphorus compound, other flame retardant, and optionally used reactive diluent of the curable resin composition. If the phosphorus content is less than 0.1% by mass, the flame retardancy of the curable resin composition may be significantly reduced. On the other hand, if the phosphorus content is more than 5% by mass, the water resistance of the curable resin composition may be significantly reduced.

[0080] 6. Other Ingredients The curable resin composition of the present invention may contain an organic solvent as a viscosity modifier, if necessary. Examples of the organic solvent include amides such as N,N-dimethylformamide; ethers such as ethylene glycol monomethyl ether; ketones such as acetone and methyl ethyl ketone; alcohols such as methanol and ethanol; and aromatic hydrocarbons such as benzene and toluene. These organic solvents may be used alone or in combination of two or more. The content of the organic solvent may be, for example, in the range of 1% by mass to 90% by mass with respect to the total mass of the epoxy resin, curing agent, crystals of the phosphorus compound, other flame retardants, and optionally used reactive diluents of the curable resin composition.

[0081] The curable resin composition of the present invention may contain an inorganic filler as necessary. Examples of such inorganic fillers include silica such as fused silica and crystalline silica; powders such as magnesium hydroxide, aluminum hydroxide, zinc molybdate, calcium carbonate, silicon carbonate, calcium silicate, potassium titanate, beryllia, zirconia, zircon, fosterite, steatite, spinel, mullite, and titania, or beads obtained by sphering these, and glass fibers. These inorganic fillers may be used alone or in combination of two or more. The content of the inorganic filler may be, for example, in the range of 30% by mass to 200% by mass with respect to the total mass of the epoxy resin, the curing agent, the phosphorus compound, and other flame retardants.

[0082] In the present invention, it is preferable to use different inorganic fillers depending on the application. For laminate applications, it is preferable to use fused silica, aluminum hydroxide, etc. For sealant applications, it is preferable to use fused silica, crystalline silica, etc., and it is more preferable to use fused silica. For casting applications, it is preferable to use fused silica, crystalline silica, aluminum hydroxide, etc., and it is more preferable to use fused silica.

[0083] The curable resin composition of the present invention may further contain additives other than the inorganic fillers as necessary. Examples of the additives include non-reactive diluents (plasticizers) such as dioctyl phthalate, dibutyl phthalate, benzyl alcohol, and coal tar; fibrous fillers such as glass fiber, pulp fiber, synthetic fiber, and ceramic fiber; reinforcing materials such as glass cloth, aramid cloth, and carbon fiber; pigments; γ-aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropyltriethoxysilane, N-β-(aminoethyl)-N'-β-(aminoethyl)-γ-aminopropyltriethoxysilane, γ-anilinopropyltriethoxysilane, γ-glycidoxypropyltriethoxysilane, β-(3,4-epoxycyclohexyl)ethyltriethoxysilane, vinyltriethoxysilane, and the like. Examples of the additives include silane coupling agents such as silane, N-β-(N-vinylbenzylaminoethyl)-γ-aminopropyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-chloropropyltrimethoxysilane, and γ-mercaptopropyltrimethoxysilane; lubricants such as candelilla wax, carnauba wax, Japan wax, Ibota wax, beeswax, lanolin, spermaceti, montan wax, petroleum wax, aliphatic wax, aliphatic esters, aliphatic ethers, aromatic esters, and aromatic ethers; thickeners; thixotropic agents; antioxidants; light stabilizers; ultraviolet absorbers; defoamers; rust inhibitors; colloidal silica, colloidal alumina, and other commonly used additives. In the present invention, adhesive resins such as xylene resins and petroleum resins may be used in combination.

[0084] The curable resin composition of the present invention can be used in laminates used in electronic circuit boards, sealing materials used in electronic components, casting materials, film materials, adhesives, electrical insulating paints, composite materials requiring flame retardancy, powder paints, flooring materials, anti-rust paints, concrete repair materials, and the like, and is particularly suitable for use in laminates, semiconductor sealing materials, interlayer insulating films, and resin-coated copper foils. EXAMPLES

[0085] EXAMPLES Next, the present invention will be described in more detail with reference to examples and comparative examples, but the present invention is not limited to these examples in any way.

[0086] [Production Example 1] In a 500mL round-bottom flask equipped with a stirring blade, a reflux tube, a thermometer and a nitrogen inlet, 114.1g (0.5mol) of bisphenol A, 276.0g (1.8mol) of phosphoryl chloride and 0.5g (0.005mol) of magnesium chloride were placed, heated until the reaction solution refluxed and stirred for 8 hours. At that time, hydrogen chloride gas generated by the reaction was trapped by introducing it into the aqueous sodium hydroxide solution from the top of the reflux tube. After the reaction, the excess amount of phosphoryl chloride was removed under reduced pressure to obtain 224.1g of phosphorus compound 1. 224.1g of toluene was added to the obtained phosphorus compound 1 to dissolve phosphorus compound 1, and a toluene solution of phosphorus compound 1 was obtained. A 1 L round bottom flask equipped with a stirring blade, reflux tube, dropping funnel and thermometer was charged with 342.9 g (4.4 mol) of 40% methylamine aqueous solution. While stirring and cooling under a nitrogen atmosphere, 448.2 g of a toluene solution of phosphorus compound 1 was dropped so that the reaction temperature did not exceed 30°C, and after the dropwise addition was completed, stirring was continued for 1 hour. After the reaction was completed, the reaction solution was transferred to a separatory funnel and extracted with 600 g of chloroform to obtain an organic layer. The obtained organic layer was washed three times with 70 g of distilled water, and the solvent was removed under reduced pressure to obtain 199 g of phosphorus compound 2 as a pale yellow solid. The obtained phosphorus compound 2 1 H NMR spectrum and 31 The P NMR spectra are shown in Figures 1 and 2. The obtained phosphorus compound 2 was a block-like solid. The NMR measurements were carried out under the following conditions. 1 H NMR, 31 P NMR analyzer: JNM ECX-400 (manufactured by JEOL Ltd.) Magnetic field strength: 400MHz 1 H-NMR integration times: 8 31 P-NMR integration times: 100 times Measurement temperature: 25℃ Deuterated solvent: Chloroform-d1 (deuteration rate 99.8%), TMS 0.03 vol.% added) (Kanto Chemical Co., Ltd.)

[0087] [Example 1] Production of phosphorus compound crystals (powder) In a 500 mL flask equipped with a stirring blade, a reflux condenser, and a thermometer, 100.0 g of phosphorus compound 2 and 10.0 g of methanol were placed, heated to 85°C, and stirred until the contents became uniform. After cooling to 80°C, 200.0 g of methyl isobutyl ketone (MIBK) was added dropwise over 30 minutes. After the addition was completed, the mixture was cooled to 25°C over 2 hours while stirring, and further stirred for 1 hour. The obtained slurry was filtered under reduced pressure, and the obtained solid was dried under reduced pressure to obtain 82.8 g of a white powder of phosphorus compound crystals. 1 H NMR spectrum and 31 The P NMR spectra are shown in Figures 3 and 4. The NMR measurement conditions were the same as in Production Example 1.

[0088] [Comparative Example 1] Production of phosphorus compound powder The phosphorus compound 2 obtained in Production Example 1 was pulverized in a mortar to obtain a white powder.

[0089] (Powder X-ray diffraction) Using a powder X-ray diffractometer (manufactured by Rigaku Corporation), powder X-ray diffraction was performed on the crystal of the phosphorus compound obtained in Example 1 and the fine powder of the phosphorus compound obtained in Comparative Example 1 under the measurement conditions of output: 1.6 kW, radiation source: Cu, wavelength: 1.541836 Å, tube voltage: 40 kV, tube current: 40 mA, sampling interval: 0.020°, and scan speed: 4,000° / min. The powder X-ray diffraction patterns of the crystal of the phosphorus compound obtained in Example 1 and the fine powder of the phosphorus compound obtained in Comparative Example 1 are shown in Figures 5 and 6, respectively.

[0090] The X-ray diffraction peaks in Figure 5 (intensities (cps) are shown in parentheses) are 5.76° (307), 8.86° (490), 10.58° (1307), 13.36° (1027), 15.78° (1423), 16.36° (2313), 17.76° (1363), 20.42° (627), 21.2° (1317), and 23.42° (813). Therefore, the maximum peak intensities are as follows: Maximum peak intensity at 2θ of 10.50° to 10.70° (C): 1307 Maximum peak intensity (D) at 2θ of 13.20° to 13.50°: 1027 Maximum peak intensity (E) at 2θ of 15.50° to 15.90°: 1423 Maximum peak intensity (A) at 2θ of 16.00° to 16.80°: 2313 Maximum peak intensity (B) at 2θ of 17.40° to 18.20°: 1363 Maximum peak intensity (F) between 20.00° and 21.50° 2θ: 1317

[0091] The X-ray diffraction peaks in Figure 6 (intensities (cps) are shown in parentheses) were 10.60° (27), 13.30° (37), 15.58° (57), 16.62° (90), 18.12° (63), and 20.08° (50). Therefore, the maximum peak intensities are as follows: Maximum peak intensity at 2θ between 10.50° and 10.70° (C): 27 Maximum peak intensity (D) at 2θ of 13.20° to 13.50°: 37 Maximum peak intensity (E) at 2θ of 15.50° to 15.90°: 57 Maximum peak intensity (A) at 2θ of 16.00° to 16.80°: 90 Maximum peak intensity (B) at 2θ of 17.40° to 18.20°: 63 Maximum peak intensity (F) at 2θ of 20.00° to 21.50°: 50

[0092] For the powders obtained in the examples and comparative examples, the ratio (A / B) of the maximum peak intensity (A) within the range of a diffraction angle (2θ) of 16.00 ° to 16.80 ° to the maximum peak intensity (B) within the range of a diffraction angle (2θ) of 17.40 ° to 18.20 ° in the diffraction pattern obtained by X-ray diffraction, the ratio (C / B) of the maximum peak intensity (C) within the range of a diffraction angle (2θ) of 10.50 ° to 10.70 °, the ratio (D / B) of the maximum peak intensity (D) within the range of a diffraction angle (2θ) of 13.20 ° to 13.50 °, the ratio (E / B) of the maximum peak intensity (E) within the range of a diffraction angle (2θ) of 15.50 ° to 15.90 °, and the ratio (F / B) of the maximum peak intensity (F) within the range of a diffraction angle (2θ) of 20.00 ° to 21.50 ° were calculated, and the results are summarized in Table 1.

[0093] [Table 1]

[0094] [Evaluation results] The following evaluations were carried out using the crystals of the phosphorus compound of Example 1 and the fine powder of the phosphorus compound of Comparative Example 1 as samples. The results are shown in Table 2.

[0095] (deliquescent) 100 g of the sample was taken and placed in a 225 ml beaker, and the opening of the beaker was covered with nonwoven fabric to prevent water droplets and dust from getting in. This test specimen was left in a thermostatic chamber (temperature 40°C, humidity 75% RH) and the presence or absence of stickiness of the sample after leaving it for 120 hours was confirmed.

[0096] (Angle of repose) Using a multi-function powder property measuring instrument MT-1001K (manufactured by Seishin Enterprise Co., Ltd.), the sample was passed through a sieve with 710 μm openings and dropped through a funnel onto a table for measuring the angle of repose. The angle of repose was measured when the shape of the pile stabilized.

[0097] (Average particle size / maximum particle size) The sample was dispersed in a mixture of heptane / Newcol (registered trademark) 80 (manufactured by Nippon Nyukazai Co., Ltd.) using a laser diffraction / scattering particle distribution measuring device LA-950 (manufactured by Horiba, Ltd.) to measure the particle size.

[0098] (Thermogravimetric reduction) Using a thermogravimetric differential thermal analyzer TG / DTA7200 (manufactured by SII NanoTechnology Inc.), the sample was heated from 30°C to 140°C at a rate of 10°C / min under a nitrogen atmosphere, and the thermal weight loss (mass%) of the sample was measured 2 hours after reaching 140°C.

[0099] (Melting Point) Using a thermogravimetric differential thermal analyzer TG / DTA7200 (manufactured by SII NanoTechnology Inc.), the sample was heated from 30°C to 550°C at a rate of 10°C / min under a nitrogen atmosphere, and the temperature at which an endothermic peak was observed in the DTA curve was determined as the melting point of the sample.

[0100] [Table 2]

[0101] The crystals of the phosphorus compound in Example 1 were excellent in handleability, such as not being deliquescent and having a small angle of repose, whereas the fine powder of the phosphorus compound in Comparative Example 1 was poor in handleability, such as being deliquescent and having a large angle of repose. [Industrial Applicability]

[0102] The crystals of the phosphorus compound of the present invention are easy to handle and are therefore useful as a flame retardant for epoxy resins.

Claims

1. A crystalline phosphorus compound represented by the following formula (1), in which a ratio (A / B) of a maximum peak intensity (A) within a diffraction angle (2θ) range of 16.00° to 16.80° to a maximum peak intensity (B) within a diffraction angle (2θ) range of 17.40° to 18.20° in a diffraction pattern obtained by X-ray diffraction is 1.50 or more and 3.00 or less. 【Chemistry 1】 (In the formula, n represents 0 or a positive number.)

2. 2. The phosphorus compound crystal according to claim 1, wherein a ratio (C / B) of a maximum peak intensity (C) within a diffraction angle (2θ) range of 10.50° to 10.70° to the maximum peak intensity (B) is 0.50 or more and 2.00 or less.

3. A step of dropping an organic solvent that is a poor solvent for the phosphorus compound while heating and stirring a phosphorus compound represented by the following formula (1) and an organic solvent that is a good solvent for the phosphorus compound: a step of dropping an organic solvent that is a poor solvent for the phosphorus compound, followed by filtering under reduced pressure and drying; A method for producing a crystal of a phosphorus compound represented by the following formula (1): 【Chemistry 2】 (In the formula, n represents 0 or a positive number.)

Citation Information

Patent Citations

  • Halogen-free flame retardant epoxy resin composition, and prepreg, laminated board, copper-clad laminated board and printed circuit board containing the same

    JP2004051907A

  • Flame-retardant thermoplastic polyester resin composition and molded article

    JP2010037375A

  • Phosphorus-containing compound, and curable epoxy resin composition containing same

    WO2015049965A1